Entre o claro e o escuro: uma poética da angústia em Saramago - Biziak, Jacob dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
By thinking about the artistic representation specificity of the contemporary novelistic fiction, we understand that there is a new attitude towards what reality and its possibilities of gaining an outline through language would be. Thus, this research aims at articulating the mimesis that is undertaken by contemporary novel and the narrator's behavior. Therefore, a questioning occurs - which is, many times, a linguistic one - about the reality created by diegesis. The narrator promotes a bordering more than filling the meaning, which led us to the idea that the narration of the contemporary novel is structured as anguish. So, we believe that the narrator is the central narrative element for us to access the construction of the reality presented by the contemporary novelistic fiction. In view of that, we have chosen anguish as an affection mostly present inside this novel, not only as a theme, but also as component of the diegetic structure. Given this situation, we have chosen two novels by Saramago that belong to different phases of the writer's work, História do Cerco de Lisboa and Ensaio sobre a cegueira - as an exercise of analysis within the previously described proposal. Finally, this research seeks not only to contribute with studies about the contemporary novel, but also about the functioning of the narrator in face of the task of representing a reality. To what concerns methodology, the work of Luiz Costa Lima is essential to our study about mimesis, mainly because of the diachronic trajectory he proposes at the same time he reviews his own postulations about the issue. The work of Genette is the basis that allowed us to evolve in our studies regarding the narrator. In relation to anguish, the work of three thinkers is central to us: Kierkegaard, Freud and Lacan (besides works about art interpretation by the same authors)

Pensando na especificidade da representação artística do ficcão romanesca contemporânea, entendemos que há uma nova postura diante do que seria a realidade e das suas possibilidades de ganhar contorno pela linguagem. Sendo assim, esta pesquisa busca articular a mimesis empreeendida pelo romance contemporåneo e o comportamento do narrador. Logo, ocorre um questionamento - muitas vezes, metalinguístico - do real criado pela diegese. O narrador promove mais um bordeamento do que um preenchimento de sentido; o que nos levou à ideia de que a narração do romance contemporâneo se estrutura como angústia. Então, acreditamos que o narrador é o elemento narrativo central para termos acesso à construção da realidade apresentada pela ficção romanesca contemporânea. Diante disso, elegemos a angústia como afeto majoritariamente presente dentro deste romance, não só enquanto tema, mas também como constituinte da estrutura diegética. Dada esta situação, escolhemos dois romances de Saramago - pertencentes a fases distintas da obra do escritor, História do cerco de Lisboa e Ensaio sobre a cegueira - como exercício de análise dentro da proposta descrita anteriormente. Por fim, esta pesquisa busca não somente contribuir com estudos a respeito do romance contemporâneo, mas também sobre o funcionamento do narrador diante da tarefa de representar uma realidade. A respeito da metodologia, sobre a mimesis, a obra de Luiz Costa Lima é fundamental ao trabalho; principalmente pelo percurso diacrônico que propõe, ao mesmo tempo em que revê suas próprias postulações sobre o assunto. A obra de Genette é a base que permitiu fazer os estudos sobre narrador evoluírem em nosso trabalho. Sobre a angústia, são centrais as obras de três pensadores: Kierkegaard, Freud e Lacan (além de obras de intepretação da arte a partir destes mesmo autores)
Keywords: Saramago, José 1922-2010; Filosofia; Psicanálise; Angústia; Philosophy